Applicability of the Rapid Biophysical Profile in Antepartum Fetal Well-Being Assessment in High-Risk Pregnancies from a University Hospital in São Paulo, Brazil: Preliminary Results. (26th June 2013) - Czeresnia, Jonathan Mamber; Araujo Júnior, Edward; Cordioli, Eduardo; Martins, Wellington P.; Nardozza, Luciano Marcondes Machado; Moron, Antonio Fernandes
Abstract : Objective . To evaluate the clinical applicability of the rapid biophysical profile (rBPP), comparing results of the rBPP to umbilical cord pH values and Apgar scores. Methods . A cross-sectional study was conducted with 37 pregnant women from our high-risk service. All of them gave birth at our institution. rBPP was conducted up to 24 h prior to delivery and pH values were obtained from the umbilical vein immediately after birth. The mean and standard deviations for maternal age, gestational age at birth, pH values, and Apgar score in the 1st and 5th minutes after birth were calculated. An unpaired Student's t -test was applied to evaluate the correlation between these variables and rBPP scores of 2 and 4. Results . rBPP score of 2 was observed in 8 patients (21.6%) and score 4 was observed in 29 cases (78.4%). No patients received score zero. The difference between the Apgar scores of the rBPP score 2 and 4 was statistically significant (P < 0.01 ) while the same was not true with the umbilical cord pH (P = 0.08 ), even though the values tended to be lower in the rBPP 2 group. Conclusion . The rBPP is a fast and practical method of assessment of antepartum fetal well-being. Further studies, with a larger number of patients, are necessary to evaluate the applicability of the method.